Evaluation of Knowledge, Awareness, and Practices of General Dental Practitioners in West Bengal Regarding Radiation Hazards and Protection: A Cross-sectional Questionnaire-based Survey - Debanti Giri; Rritam Ghosh; Sayan Chattopadhyay; Debasree Boral; Kanad Chaudhuri (Journal of Indian Academy of Oral Medicine and Radiology)
Background: Radiation exposure from dental radiographic procedures, though minimal, can accumulate over time, necessitating adherence to safety guidelines to mitigate potential biological effects. Objective: The present study aimed to assess the awareness and practices of radiation safety among general dental practitioners (GDPs) in the state of West Bengal. Methods: For the current prospective cross-sectional study, a self-structured questionnaire, containing 18 questions after checking for proper validity and reliability was sent to 400 dentists. Pearson Chi-square test was carried out to assess the statistical significance. A P value of ≤0.05 was considered as the level of significance. Results: The overall response rate of the survey was 62.25% (249 responses). In total, 81.1.% were aware of the as low as reasonably achievable principle, although only 36.9% used protection equipment like a lead apron/thyroid collar for themselves and 33.3% used it for their patients. In total, 91.2% used an X-ray machine approved by the Atomic Energy Regulatory Board, while only 34.9% acknowledged having registered themselves and their clinical staff for thermoluminescent dosimeter badges. Conclusion: Conducting various Continuing Dental education programs is necessary to give practitioners better exposure to radiation safety and its application, ensuring their application of radiation safety measures in their clinical practice.